2016
DOI: 10.1038/srep37368
|View full text |Cite
|
Sign up to set email alerts
|

In-situ growth of MnO2 crystals under nanopore-constraint in carbon nanofibers and their electrochemical performance

Abstract: Growing MnO2 nanocrystals in the bulk of porous carbon nanofibers is conducted in a KMnO4 aqueous solution aimed to enhance the electrochemical performance of MnO2. The rate of redox reaction between KMnO4 and carbon was controlled by the concentration of KMnO4 in a neutral solution. The MnO2 nanoparticles grow along with (211) crystal faces when the redox reaction happens on the surface of fibers under 1D constraint, while the nanoparticles grow along with (200) crystal faces when the redox reaction happens i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…The straight line witnessed along the imaginary axis corresponds to the polarizable capacitance 15 . Moreover, no significant IR drop in GCD curves also validates the ideal capacitive behavior of the synthesized composite membrane which could be credited to the higher ionic conductivity and relatively improved electrolyte uptake as compared CNF 45 .…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The straight line witnessed along the imaginary axis corresponds to the polarizable capacitance 15 . Moreover, no significant IR drop in GCD curves also validates the ideal capacitive behavior of the synthesized composite membrane which could be credited to the higher ionic conductivity and relatively improved electrolyte uptake as compared CNF 45 .…”
Section: Resultssupporting
confidence: 55%
“…High resolution XPS spectra of individual elements are illustrated in Figure S9 . The binding energy separation of 11 eV between the peaks at 653 and 642 eV attributed to Mn 2p 1/2 and Mn 2p 3/2 , respectively, and separation energy of 4.9 eV of Mn 3 s spin orbit doublet 45 confirmed the intermediate state of Mn (Figure S9 ). It could be observed that Mn 2p 1/2 and Mn 2p 3/2 peaks declined after cyclic performance which validated the structural deformation of Mn at nanoscale, thus, may be credited for 15% loss of specific capacitance for after 2000 GCD cycles.…”
Section: Resultsmentioning
confidence: 70%
“…Carbon and manganese oxide composites have been attracting much attention in the search for good preparation methods and improved electrochemical performance . Different from previous reports, herein, HCF/Mn 3 O 4 prepared by in situ synthesis exhibits a special nanostructure that is favorable for achieving excellent cycling stability and rate performance for LIBs.…”
Section: Resultsmentioning
confidence: 99%
“…MnO 2 nanocrystals conned into nanopores of porous carbon nanobers (CNFs) delivered high electrochemical capacitance in 1 M Na 2 SO 4 aqueous electrolyte, the electrodes of the MnO 2 / CNF composite giving the capacitance of 1282 F g À1 with the current density of 0.2 A g À1 . 52 Porous CNFs were synthesized from the mixture of polyimide with polyvinylpyrrolidone (PVP) via electrospinning, followed by carbonization. In order to conne MnO 2 nanocrystals preferentially in the nanopores, the porous CNFs had to be immersed into the KMnO 4 aqueous solution with the concentration of less than 0.024 g L À1 , while higher concentration of KMnO 4 solution resulted in MnO 2 deposition mostly on the external surface of the CNF.…”
Section: (B) Inorganicsmentioning
confidence: 99%